1980
DOI: 10.1002/1097-0142(19800415)45:8<2188::aid-cncr2820450830>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse histiocytic lymphoma presenting with gastrointestinal tract lesions the stanford experience

Abstract: The medical records of all patients with diffuse histiocytic lymphoma (DHL) presenting for treatment at the Stanford University Medical Center between 1970-1978 were reviewed. From this group of 284 patients, 48 were identified with gastrointestinal tract lesions at initial evaluation. Abdominal pain was the most common presenting symptom. Anorexia, weight loss, malaise, and weakness were also common complaints. Twenty percent of these patients noted abdominal masses and 15% experienced gastrointestinal bleedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0
1

Year Published

1981
1981
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(27 citation statements)
references
References 34 publications
4
22
0
1
Order By: Relevance
“…Our experience of the use of multichemotherapy as primary treatment in patients with unresected tumours has been similar to that reported in the literature (Hande et al, 1978;Rosenfelt & Rosenberg, 1980). Only 3 out of 9 such patients i.e.…”
Section: Survivalsupporting
confidence: 84%
See 2 more Smart Citations
“…Our experience of the use of multichemotherapy as primary treatment in patients with unresected tumours has been similar to that reported in the literature (Hande et al, 1978;Rosenfelt & Rosenberg, 1980). Only 3 out of 9 such patients i.e.…”
Section: Survivalsupporting
confidence: 84%
“…Although we do not disagree with the statement that the application of the Ann-Arbor system is problematic in some cases of lymphomas, its modified from used in our study proved to be quite useful as a prognostic determinant, in accordance with the findings of others (Rosenfelt & Rosenberg, 1980;Hermann et al, 1980;Weingrand et al, 1982).…”
Section: Survivalsupporting
confidence: 81%
See 1 more Smart Citation
“…Non-Hodgkin's lymphomas (NHLs) are known to arise from extranodal sites with an estimated frequency of 10-30% (Banfi et al, 1968;Freeman et al, 1972;Jones et al, 1973;Rudders et al, 1978;Reddy et al, 1980;Ho et al, 1984;Gospodarowicz et al, 1987). The gastrointestinal tract is the site most frequently affected at diagnosis accounting for about 4-18% of all extranodal forms of NHLs (Freeman et al, 1972;Reddy et al, 1980;Ho et al, 1984;Lewin et al, 1978;Isaacson et al, 1979;Herrmann et al, 1980;Hande et al, 1978;Strauss et al, 1983;Gospodarowicz et al, 1983;Siegert et al, 1985;Carnevali et al, 1987).…”
mentioning
confidence: 99%
“…The role of surgery in the management of PGL is to ensure an accurate histopathological diagnosis, reduce tumour bulk, relieve symptoms and prevent bleeding and perforation. Although the actual frequency of chemotherapy-related bleeding or perforation is not clear, the frequency of these complications in unresected patients with gastrointestinal lymphoma reported previously varies from 0% to 20% (Brooks et al, 1983;Gobbi et al, 1984;Rosenfelt et al, 1980). Another important aspect of surgery is tumour staging, and many authors have reported that this is the most important prognostic factor affecting survival (Lim et al, 1977;Shiu et al, 1982;Brooks et al, 1983;Dragosics et al, 1985;Hockey et al, 1987) Any additional treatment is based on the pathological stage, and surgical exploration with gastrectomy is the only means of achieving this.…”
Section: Discussionmentioning
confidence: 99%